How Budgeting Practices Influence Financial Stability Among University Students - Kok Ban Teoh; Syazwina Nadiah Binti Zulkurnein; Yinghao Sun; Syamimi Izzureen Binti Shahrin; Syarifah Nur Adawiyah Binti Syed Rizaudi; Peehu Goyal; Daisy Mui Hung Kee (AIBPM Publisher, 2026)
This study examines the determinants of financial stability among university students by positioning budgeting practices as a mediating mechanism within the cognition–behavior–outcome framework. Specifically, it investigates the effects of financial literacy, financial attitudes, and social norms on budgeting practices and financial stability. A quantitative approach was employed using an online survey distributed to 205 university students from several higher education institutions. Data were analyzed using descriptive statistics, correlation, and regression analysis. The results indicate that financial literacy (? = 0.444, p 0.001) and financial attitudes (? = 0.216, p 0.001) significantly influence budgeting practices, while budgeting practices strongly predict financial stability (? = 0.539, p 0.001). Although financial literacy and financial attitudes do not directly affect financial stability, social norms demonstrate a significant direct effect (? = 0.322, p 0.05). The model explains 34.8% of the variance in financial stability. Overall, the findings highlight budgeting practices as the key behavioral mechanism linking financial competence to improved financial stability, suggesting that universities should strengthen experiential financial education to enhance students’ financial resilience.